Occlusal Schemes during Eccentric Jaw Movements in Dental Students of Lahore Medical and Dental College, Lahore - Syed Hammad Azeem Rizvi, Faiqua Yasser, Afsheen Zakir, Faiza Awais, Anam Shaukat, Muhammad Umair Iqbal, Sajid Naeem (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Occlusion plays an important role in the health of stomatognathic system. Care full designing and rehabilitation of occlusal scheme in restoring lost dentition is required. Aim: To find out the occlusal schemes and to study the nature of occlusal contacts during maximum intercuspation to protrusive and lateral excursions. Study design: A cross-sectional observational study. Place & duration: Prosthodontic Department, Lahore Medical and Dental College from 10th Jul ‘21 to 10th October’21. Methodology: A total of 104 dental students were selected and their occlusal schemes were classified. Participants occlusal interferences i.e; centric, protrusive, mediotrusive and laterotrusive were also recorded using shim stocks, diagnostic instrument and by visual assessment. Horizontal and vertical overlap of anterior teeth was also measured. Results: Among 104 participants studied, 61.5% were found having canine guided occlusal scheme, 29.8% having group function whereas 8.7% had the combination of both. Majority participants do not have any occlusal interference 79.8%, whereas 20.2% were having interferences out of which the group function occlusal scheme had maximum number of interferences,10(9.6%). Insignificant relationship was obtained between presence of interferences and occlusal schemes, P>0.05. The type of interference most commonly seen was the protrusive interferences (37.5%). Conclusion: The type of occlusal scheme commonly observed is canine guided occlusion, however there were no occlusal factors that were significantly associated to any particular occlusal scheme.